Prevalence of serological markers and nucleic acid for blood-borne viral infections in blood donors in Al-Baha, Saudi Arabia - AlMutairi, Hatem H; AlAhmari, Mohammad M; Al-Zahran, Badr H; Abbas, Ibrahim S; Al Ghamdi, Juma`an S; Raja`a, Yahia A; Sallam, Talal A (The Journal of Infection in Developing Countries, 2016)
Introduction: Data on blood-borne viral infections in some regions in Saudi Arabia remain scarce. This study investigates the prevalence of serological markers and nucleic acid for blood-borne viruses among blood donors in Al-Baha, Kingdom of Saudi Arabia. Methodology: In this cross-sectional study, 2,807 donors who donated blood between January 2009 and November 2011 were investigated for blood-borne viral serological markers including HBsAg, anti-HBc, anti-HBs, anti-HCV, anti-HIV, and anti-HTLVI/III in addition to viral nucleic acid. Results: All donors were males between 16 to 66 years of age (mean: 31.5 ± 9.3 years). Viral nucleic acid and/or serological markers were detected in a total of 36 (1.3%) donors; of them, 26 (72.2%) had nucleic acid concomitant with serological markers, 6 (16.7%) had only viral nucleic acid, while 4 (11.1%) had only serological markers. Of all donors, 22 (0.8%) had HBsAg, 227 (8.0%) had anti-HBc, 157 (5.0%) had anti-HBs, 2,577 (91.8%) had no HBV markers, 2 (0.07%) had anti-HIV, 1 (0.04%) had anti-HCV, and 1 (0.04%) had anti-HTLVI/II. The donors who were born during HBV vaccination era showed no HBsAg (0.0%; p = 0.052), lower rates of anti-HBc (1.5%; p < 0.001) and anti-HBs (0.7%; p < 0.001), while the majority had no HBV markers (98.5%; p < 0.001). Conclusions: Combined viral nucleic acid and serological testing of donated blood enhances blood safety. The absence of HBV markers among donors suggests susceptibility or declined anti-HBs levels. Thus, HBV revaccination or a vaccine boost among adolescents and adults might be indispensable.